Comparison of Outcomes After Transcatheter Versus Surgical Repeat Mitral Valve Replacement - Amr A. Arafat; Ashraf I. Zahra; Abdulaziz Alhossan; Haneen Alghosoon; Mohammad Alotaiby; Monirah A. Albabtain; Adam I. Adam; Khaled D. Algarni (Brazilian Journal of Cardiovascular Surgery, 2022)
ABSTRACT Introduction: Repeat transcatheter mitral valve replacement (rTMVR) has emerged as a new option for the management of high-risk patients unsuitable for repeat surgical mitral valve replacement (rSMVR). The aim of this study was to compare hospital outcomes, survival, and reoperations after rTMVR versus surgical mitral valve replacement. Methods: We compared patients who underwent rTMVR (n=22) from 2017 to 2019 (Group 1) to patients who underwent rSMVR (n=98) with or without tricuspid valve surgery from 2009 to 2019 (Group 2). We excluded patients who underwent a concomitant transcatheter aortic valve replacement or other concomitant surgery. Results: Patients in Group 1 were significantly older (72.5 [67-78] vs. 57 [52-64] years, P<0.001). There was no diference in EuroSCORE II between groups (6.56 [5.47-8.04] vs. 6.74 [4.28-11.84], P=0.86). Implanted valve size was 26 (26-29) mm in Group 1 and 25 (25-27) mm in Group 2 (P=0.106). There was no diference in operative mortality between groups (P=0.46). However, intensive care unit (ICU) and hospital stays were shorter in Group 1 (P=0.03 and <0.001, respectively). NYHA class improved significantly in both groups at one year (P<0.001 for both groups). There was no group effect on survival (P=0.84) or cardiac readmission (P=0.26). However, reoperations were more frequent in Group 1 (P=0.01). Conclusion: Transcatheter mitral valve-in-valve could shorten ICU and hospital stay compared to rSMVR with a comparable mortality rate. rTMVR is a safe procedure; however, it has a higher risk of reoperation. rTMVR can be an option in selected high-risk patients.